Polymer/Nanodiamond Composites in Li-Ion Batteries: A Review - Kausar, Ayesha; Ashraf, Rozina; Siddiq, Muhammad (Polymer-plastics technology and engineering, 2014)
Nanodiamonds have emerged as a subject of tremendous research interest in recent years due to their unique combination of properties, such as large diameter, small and accessible surface, and excellent mechanical properties. Outstanding performance of these nanocomposites basically arises from their structure. When incorporated appropriately, this carbon nanomaterial can remarkably improve physical characteristics of polymer matrix even at extremely small loading content. Physical techniques summarizing thermal, morphological, mechanical, electrical and other properties of polymer/nanodiamond nanocomposites have been discussed. Furthermore, the review elaborates their uses in Li-ion battery, as well as current challenges associated and future prospective for this exciting class of nanocomposites.